Surface Recombination Via Interface Defects in Field Effect Transistors - E. Bendada; K. Raïs; P. Mialhe; J. P. Charles (Active and Passive Electronic Components)
Recombination current at the oxide-semiconductor interface of metal-oxide-semiconductor devices has been analyzed and compared with the experimental result. The activity of interface traps is dependent on the energy level and on the operating conditions. A model is shown to be powerful to describe the effect of energy level of bulk recombination centers on the values of reverse recombination current.